Improvisation of Magnetic Resonance Imaging (MRI) with development and feasible evaluation of fiber optic sensors: a survey - Shabnam, Farzana; Karim, Kazi Lamiyah Daraksha; Shahrear, S. M.Fardin (© 2016 IEEE, 2018)
This conference paper was published in the International Conference on Advances in Electrical, Electronic and Systems Engineering, ICAEES 2016; Putrajaya Marriott HotelPutrajaya; Malaysia; 14 November 2016 through 16 November 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICAEES.2016.7888112 The Journal's website is at: https://ieeexplore.ieee.org/document/7888112/